Produits de base - Les exportations de betail et de viande apres la secheresse au Sahel - International Livestock Centre for Africa (1979)
Development of trade in livestock and meat between countries of the sahelian zone and importing countries in west africa and central africa, with particular reference to price trends and effects of the drought on the breeding stock.